1954
DOI: 10.1016/0014-4894(54)90008-9
|View full text |Cite
|
Sign up to set email alerts
|

Germinal development in the sporocysts and rediae of the digenetic trematodes

Abstract: In the vertebrate-dwelling adults of the digenetic trematodes spermatogenesis and oogenesis are not fundamentally different from these processes in other metazoan groups. The fertilized ovum in the egg develops directly into the miracidium which contains in its body cavity a varying number of germinal cells. After entering the molluscan intermediate host the miracidium metamorphoses into the primary germinal sac, the mother sporocyst. In its body cavity the germinal cells multiply and develop into secondary ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

1956
1956
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…The undifferentiated cells could give rise to the germinal cells that, in turn, cleave to give rise to embryo cells. The same can be seen in developing rediae and daughter sporocysts (up to the point of brood sac development), when some cells in the undifferentiated central cell mass become specialized as germinal cells (the so called primary germinal cells) and begin to cleave (Cort, Ameel & Van der Woude, 1954 ;Galaktionov & Dobrovolskij, 1998).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The undifferentiated cells could give rise to the germinal cells that, in turn, cleave to give rise to embryo cells. The same can be seen in developing rediae and daughter sporocysts (up to the point of brood sac development), when some cells in the undifferentiated central cell mass become specialized as germinal cells (the so called primary germinal cells) and begin to cleave (Cort, Ameel & Van der Woude, 1954 ;Galaktionov & Dobrovolskij, 1998).…”
Section: Discussionmentioning
confidence: 85%
“…In many digeneans that have rediae in their lifecycles, and in the majority of those having daughter sporocysts, embryo development from primary germinal cells is accompanied by the formation of a specialized reproductive organ known as the germinal mass (Cort et al 1954 ;Galaktionov & Dobrovolskij, 1998). Nothing structurally similar to the germinal masses of rediae and sporocysts was found in the M1 and M2 investigated in this study.…”
Section: Discussionmentioning
confidence: 86%
“…As a general rule, many of the more primitive digenean groups have a restricted capacity for germinal cell division with small numbers of discrete, totipotent cells being formed within each germinal sac. Cort et al (1954) described limited multiplication of the germinal cells in several amphistome digeneans and this would appear to be correlated with low cercarial outputs in this group. Paramphistomum cervi and Cotylophoron cotylophorum, for instance, have been calculated to produce as few as 180 and 225 cercariae respectively from a single miracidium (Bennett, 1936).…”
Section: Productivity Of Germinal Sac Rmdtiplicationmentioning
confidence: 88%
“…With few exceptions, rediae are of 2 types: those that produce additional generations of daughter rediae, and others that give rise only to cercariae. Cort et al (1948Cort et al ( , 1954 Although a number of cercariae of the pleurolophocercous and closely related types have been described, those for specific trematodes of the family Heterophyidae are few. Sonsino in 1892 described Cercaria pleurolophocerca from a freshwater snail in Egypt.…”
Section: And His Colleagues Have Emphasized the Importance Of A Knowlmentioning
confidence: 97%
“…Observation of the formation of germinal material at 2 sites in the redia is not entirely new Cort et al (1948). have shown that germinal masses consisting of unicellular and multicellular components may occur in the lateral as well as posterior walls of the body cavity in the mother rediae of Notocotylus urbanensis and Psilostomum ondatrae.…”
mentioning
confidence: 98%